Risk factors increasing the incidence of multiple sclerosis (MS) - Monika Kuc; Agnieszka Siedlak; Katarzyna Cyboran; Dominik Machaj; Alicja Płaczek (Kazimierz Wielki University, 2022)
Multiple sclerosis is a chronic demyelinating disease. The etiology of MS is complex and can be associated with many different factors acting simultaneously or in a cascade. There is ample evidence that latitude, light and vitamin D exposure, and migration have a major influence on the incidence of MS. This shows the uneven distribution of the sick population across the globe. The participation of environmental factors such as bacteria and viruses as well as smoking is not excluded.